Glycomimetic antagonists of BC2L-C lectin: insights from molecular dynamics simulations - Antonini, Giulia; Civera, Monica; Lal, Kanhaya; Mazzotta, Sarah; Varrot, Annabelle; Bernardi, Anna; Belvisi, Laura (Frontiers in Molecular Biosciences, 2023)
Opportunistic infections from multidrug-resistant pathogens such as Burkholderia cenocepacia are a threatening risk for hospital-bound patients suffering from immunocompromised conditions or cystic fibrosis. B. cenocepacia BC2L-C lectin has been linked to bacterial adhesion and biofilm formation, thus hindering its activity is seen as a promising strategy to reduce the severity of the infection. We recently described the first bifunctional ligands of the trimeric N-terminal domain of BC2L-C (BC2L-C –Nt), capable of simultaneously engaging its fucose-specific sugar binding site and a vicinal region at the interface of two monomers. Here, we report a computational workflow for the study of these glycomimetic bifunctional ligands in complex with BC2L-C-Nt, aimed at investigating the molecular basis of ligand binding and the dynamics of glycomimetic/lectin interactions. In particular, we evaluated the use of molecular docking in the protein trimer, followed by refinement using MM-GBSA re-scoring and MD simulations in explicit water. Computational results were compared to experimental data derived from X-ray crystallography and isothermal titration calorimetry. The computational protocol proved suitable to provide a reliable description of the interactions between the ligands and BC2L-C-Nt, highlighting the contribution of MD simulations in explicit solvent for a good fit with the experimental observations. The information achieved in the study and the whole workflow appear promising for the structure-based design of improved BC2L-C-Nt ligands as novel antimicrobials with antiadhesive properties.